ANALISIS PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN PERBANKAN YANG GO PUBLIC DI BURSA EFEK INDONESIA SEBELUM DAN SETELAH MERGER DAN AKUISISI PERIODE TAHUN 2000-2012 - Efni, Yulia (Jurnal Tepak Manajemen Bisnis, 2014)
The purpose of this research to investigate the banking performance in Indonesia before and after the implementation of mergers and acquisitions by assessing 3 years before and 3 years after the merger and acquisition. The population included all the banks doing merger and acquisition from 2000 to 2012 are 15 companies. The sample involved 7 merging and acquiring banks generated from purposive sampling method. The research data were analyzed with Wilcoxon test. The results show that the CAR variable unsignificant difference in performance before and after mergers and acquisitions, in contrast with other variables there are significant differences on NPL, ROA, BOPO and LDR variable before and after mergers and acquisitions.Keywords : merger dan acquisition, bank, CAR,NPL,ROA,BOPO,LDR, Wilcoxon